Polarization-insensitive self-collimation and beam splitter based on triangular-lattice annular photonic crystals - Jiang, Liyong. (2014)
This paper systematically investigates the self-collimation behavior in silicon-based triangular-lattice annular photonic crystals (PCs). It is found that, in comparison with normal air-hole PCs, annular PCs more easily suppress the separation between TE-2 and TM-2 bands along the Γ-M direction by increasing the inner radius of annular air rings. Such a feature is quite beneficial in the formation of a flat equi-frequency contour for both polarizations at the same frequency, which means a polarization-insensitive self-collimation (PISC) effect. Further analysis has shown that, to support PISC, the minimum ratio between the inner and outer radii of annular air rings will gradually increase as the outer radius changes from 0.25a to 0.49a. When the ratio is fixed, the annular air rings with larger outer radius will provide wider common frequency area to realize PISC. We have also investigated the transmission feature for different annular PCs and chosen an optimal structure to illustrate the PISC effect. Finally, a polarization beam splitter has been proposed and demonstrated based on the unique PISC and band-gap feature in triangular-lattice annular PCs.